G255(P) Psychological interventions for patients of all ages with mild traumatic brain injury: A systematic review. (27th April 2016) - Creasey, NJ; Lyttle, M
Abstract : Introduction: Head injury is the commonest injury type in UK children accounting for 350, 000 Emergency Department attendances every year. While many of these are trivial a significant proportion have a mild traumatic brain injury (mTBI) which is synonymous with concussion. Symptoms can be persistent in up to 25% and can lead to psychosocial morbidity. Current management to prevent or treat persistent symptoms is variable and generally lacking. Objectives/Methods: We conducted a literature search to establish the evidence base for psychological treatment of mTBI in all age groups. We searched four electronic databases, hand-searched reference lists, and reviewed work presented at brain injury conferences. Relevant studies were selected and analysed by 2 authors. Heterogeneity of data precluded any meta-analysis. Results: 2722 abstracts and 103 full text articles were reviewed. There were 46 relevant studies of which 25 were randomised controlled trials (RCTs), 18 were studies with a pre and post intervention design and 3 were case reports. Of the 25 RCTs only 4 included children and only one included children below the age of 6 years. The RCT's could be divided into early intervention to prevent persistence of symptoms (19 studies) and later interventions for patients with persistent symptoms (6 studies). For the purposes of this review we have focussed only on early interventions. Interventions included: Phone or text messaging support (4), web based information (1), Cognitive Behavioural Therapy (1), early follow up with treatment as needed (7), education and reassurance prior to discharge (5) and psychoeducational treatment (1). Outcome measures were variable but most included measures of concussion or psychiatric symptoms. Ten studies showed improvement with interventions compared with controls and nine studies showed no difference. There were methodological flaws and possible bias in many studies and some were also limited by small sample sizes. Conclusion: Whilst there is some evidence in favour of psychological interventions, good quality evidence continues to be lacking. The variation in study particulars makes comparisons between studies difficult. There is a particular shortage of evidence in children which is surprising given the high incidence of injury and vulnerability of this group.